Weight Loss Methods in Male Combat Athletes: Effects and Differences by Discipline - Çağlar, Esin Çağla; Özkan, Rıdvan; Bayraktar, Mustafa Tolga; Uzun, Recep Nur (Ibrahim Erdemir, 2025)
Aim: This study examined the impact of weight loss methods on male combat athletes across different disciplines and in the context of pre-competition periods. Method: A total of 321 male athletes participated in the study, and data were collected using the ' Athlete Weight Loss Methods and Effects Scale.' Since the data were not normally distributed according to the Kolmogorov-Smirnov test, non-parametric analyses, including the Mann-Whitney U test and the Kruskal-Wallis test, were used. Results: The athletes lost an average of 5.86% (4.43 kg) of their normal body weight prior to competition. Significant differences were found between the competition branches in the sub-dimensions of ergogenic aid, physiological effects, and psychological effects (p